Virus transmitidos por afidos - Gálvez E., Guillermo E. (International Center for Tropical Agriculture, 1980)
There are various viruses transmitted by aphids that infect beans in almost all countries; (1) BCMV causes yield losses from 35- 98 percent according to the var., time of infection and environmental conditions. The virus can attack any part of the plant and produces 3 types of symptoms: mosaic, necrosis and local lesion resistance. BCMV particles may be transmitted mechanically, in pollen and seed from infected plants, and by insect vectors. Planting date and clean seed production are 2 cultural practices that have been used to reduce the incidence of the disease, as well as the use of resistant var. (2) BYMV can cause yield losses of up to 33 and 41 percent due to the reduction in no. of pods and seeds, resp. The BYMV host range is very wide and can cause chlorotic spots, yellow and green mottling, stunting and necrosis. Alternate hosts of BYMV should be eliminated from bean fields, and chemical control should be used to reduce aphid populations on the crops. The best control method is the utilization of resistant var. (3) Cucumber mosaic virus (CMV) is not considered of economic importance. Infection symptoms consist of a mild mosaic, vein clearing, vein banding, leaf rolling epinasty and/or apical necrosis. CMV particles are easily transmitted mechanically, in seed and by insect vectors. Among control measures are included the planting of healthy seed and crop rotation. The symptoms and damage caused by the disease are illustrated in color. (CIAT)